High prevalence of vitamin D deficiency and its association with metabolic disorders in elderly patients - Koziarska-Rościszewska, Małgorzata; Rysz, Jacek; Stępień, Mariusz (Family Medicine & Primary Care Review, 2017)
Background . Vitamin D is considered to be an important co-factor of metabolic processes. However, the available data is ambiguous. Some data indicates an important role of vitamin D in adipocyte metabolism, and hence also in obesity – a well-known risk factor of diabetes mellitus and cardiovascular diseases (CVD). Objectives . To assess the prevalence of vitamin D deficiency and to evaluate the relationship between serum 25(OH)D concentration and metabolic disorders in elderly patients attending primary care. Material and methods . This observational study was performed on 110 elderly patients: 88 females, 22 males, Caucasian, > 60 years. A questionnaire was completed concerning lifestyle and chronic diseases. Clinical examination, anthropometric measurements and laboratory tests (25(OH)D, lipids, glycemia, blood morphology, serum creatinine, PT H) were performed. BMI and WHR were calculated. Patients reporting physical activity (walking, Nordic walking, swimming, cycling, other) ≥ 150 minutes per week were classified as “physically active”. Results . Vitamin D deficiency (25(OH)D < 30 ng/ml; < 75 nmol/l) was found in 84.5%, extreme deficiency (< 10 ng/ml; < 25 nmol/l) in 6.3%. A significant correlation between serum vitamin D deficiency and visceral obesity was found (p = 0.02). No correlation was found with BMI, physical activity, lipids, diabetes or CVD. Conclusions . Vitamin D deficiency was found to be highly prevalent in the examined group of elderly people. Visceral obesity in the elderly is associated with vitamin D deficiency. Vitamin D supplementation may supposedly contribute to prevention of obesity and its treatment.